Sistematik Review: Jenis-jenis Gen yang Berpengaruh terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 - Muhammad Fathurrahman; Reski Mulia (SENTRI: Jurnal Riset Ilmiah, 2025)
Blood glucose reduction in patients with type 2 diabetes mellitus (T2DM) varies considerably among individuals, largely due to genetic factors that influence responses to antidiabetic drug therapy. This interindividual variability affects both the effectiveness and safety of commonly prescribed oral antidiabetic agents. Therefore, understanding the genetic determinants of treatment response is essential for optimizing glycemic control in patients with T2DM. This systematic review aims to identify genetic polymorphisms associated with variations in blood glucose reduction, particularly in patients receiving metformin, sulfonylureas, and other oral antidiabetic drugs. A comprehensive literature search was conducted using the PubMed, Scopus, and Google Scholar databases. A total of 880 articles were initially identified, of which 760 articles passed the preliminary screening based on title and abstract relevance. Following full-text screening using predefined inclusion and exclusion criteria, five studies were deemed eligible and included in the final analysis. The findings indicate that several genes play a major role in determining glycemic response to oral antidiabetic therapy, including SLC22A1 (OCT1), SLC22A2 (OCT2), SLC47A1 (MATE1), CYP2C9, KCNJ11, ABCC8, and TCF7L2. Genetic variations in these genes influence drug pharmacokinetics and pharmacodynamics, thereby contributing to differences in therapeutic effectiveness and glycemic outcomes among patients.